1371 "The Nosebleed Effect": Advice Given to Epistaxis Patients Discharged from The Emergency Department. (12th October 2021) - Shaladi, A; Loizou, P; Michael, M
Abstract: Introduction: Many patients with epistaxis are seen in the A&E department. A significant number are discharged without need for inpatient admission due to minor bleeds. Many are given limited information on management of further bleeds and even fewer are advised on the prevention of bleeds. Aim: To evaluate the advice given to patients with epistaxis who are seen and discharged from A+E, to instigate an improvement in advice and to examine the subsequent effect on re-attendance rates Method: Epistaxis patients discharged from A+E were audited over a 6-week period looking at advice given on discharge. A questionnaire was distributed to all A&E and ENT doctors probing current practice. A presentation on the management and prevention of epistaxis and the appropriate verbal/written advice to give was delivered and epistaxis advice sheets were made available. The practice regarding advice and the re-attendance rates were re-audited. Results: 53 patients presented to the A&E department with epistaxis. 31 patients presenting with epistaxis were seen and discharged by A&E doctors. The remaining seen by ENT. Only 9 patients received verbal advice and 1 received written advice. There were 13 re-attenders. After re-audit showed a significant increase in the proportion of patients receiving advice by A&E doctors. Verbal and written advice increased from 18% to 61% and 1% to 60% respectively. The number of re-attenders was reduced to 13 to 6.